2021
DOI: 10.3390/pharmaceutics13122001
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Predicts Drug Metabolism and Bioaccumulation by Intestinal Microbiota

Abstract: Over 150 drugs are currently recognised as being susceptible to metabolism or bioaccumulation (together described as depletion) by gastrointestinal microorganisms; however, the true number is likely higher. Microbial drug depletion is often variable between and within individuals, depending on their unique composition of gut microbiota. Such variability can lead to significant differences in pharmacokinetics, which may be associated with dosing difficulties and lack of medication response. In this study, liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The substantial metabolic capacity of the microbiome can alter the pharmacokinetics (PK) of drugs, and thus their therapeutic efficacy, via a plethora of mechanisms in a patient-specific manner [128,136,137]. The intestinal concentrations of over 150 small molecule drugs are currently known to be directly depleted by microbiota [138]. It has recently been demonstrated that gut microbiota can accumulate drugs as well as chemically transform them [139].…”
Section: The Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…The substantial metabolic capacity of the microbiome can alter the pharmacokinetics (PK) of drugs, and thus their therapeutic efficacy, via a plethora of mechanisms in a patient-specific manner [128,136,137]. The intestinal concentrations of over 150 small molecule drugs are currently known to be directly depleted by microbiota [138]. It has recently been demonstrated that gut microbiota can accumulate drugs as well as chemically transform them [139].…”
Section: The Microbiomementioning
confidence: 99%
“…Elsewhere, an ANN predicted the size and drug loading efficiency of nanoparticles based on excipient composition, resulting in more accurate predictions than a DoE model applied to the same task [272]. ML has also been leveraged to predict drug-microbiome interactions [136,138,140]. As the amount of data available to research departments continues to increase, quantum computing may supersede classical computing for ML and other in silico techniques, due to its capacity to process datasets containing hundreds of thousands of datapoints much more efficiently [273,274].…”
Section: In Silico Prediction For Colonic Drug Deliverymentioning
confidence: 99%
“…Only a small proportion of the interactions between natural drugs and GM have been elucidated, considering the huge contribution of bacterial metabolism in digestion [ 123 , 124 ]. A recent study suggested a novel solution: adopting machine learning to predict drugs’ metabolism by GM [ 125 ]. Although the model used in the study predicted the depletion of drugs by gut microbial metabolism and did not suggest any consequent metabolites, it is worth exploring the possibilities of computational analysis in this field.…”
Section: Current Status and Future Perspectivesmentioning
confidence: 99%
“…In healthcare, ML is used in clinical trials, diagnostics and surgery (Giorgio et al, 2022;Halamka et al, 2022;Myszczynska et al, 2020;Shah et al, 2019;Zame et al, 2020). In pharmaceutics, ML models have been applied to model drug-food interactions, drug-microbiome interactions, and formulation development (Gavins et al, 2022;McCoubrey et al, 2021;Wang et al, 2022). For 3D printing medicines, ML has been demonstrated to predict printability, drug release rate, and accelerating quality control (Elbadawi et al, 2020a;Muñiz Castro et al, 2021;O'Reilly et al, 2021).…”
Section: Introductionmentioning
confidence: 99%